Degradable high-transmittance protective glasses material and preparation method thereof
The biodegradable high-transparency protective eyewear material prepared by polymer copolymerization and melt co-extrusion solves the problems of insufficient biodegradability and mechanical properties of existing materials, achieving high light transmittance, strength and toughness, and self-healing ability.
Patent Information
- Application Number
- CN202511239420.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-01
- Publication Date
- 2025-11-28
AI Technical Summary
Existing protective eyewear materials struggle to combine good biodegradability, high light transmittance, and excellent mechanical properties. In particular, traditional polycarbonate materials are not sufficiently hard and brittle, polylactic acid is brittle and has poor impact resistance, and the light transmittance of polyhydroxyalkanoates needs to be improved.
A biodegradable, high-transparency protective eyewear material is prepared by copolymerizing monomers A, B, C, and D using a melt co-extrusion method. The polymer consists of 4,4'-dithiodibenzoic acid, dimethyl tetrafluoroterephthalate, dimethyl vinyl terephthalate, and bisphenol A. A crosslinking agent and an initiator are added to form a disordered and uniform molecular chain structure, which enhances flexibility and strength.
The material achieves high light transmittance, strength, toughness, and biodegradability, and possesses self-healing capabilities, meeting the requirements for use in protective eyewear.
Smart Images

Figure CN121021771A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of high polymer materials, in particular to a degradable high-transparency protective eyewear material and a preparation method thereof. BACKGROUND
[0002] Protective eyewear, as an important personal protective equipment, is widely used in industrial production, medical treatment, laboratory, outdoor sports and other scenes, and its main function is to protect eyes from dust, splashes, ultraviolet rays, chemical substances and the like. At present, the protective eyewear materials on the market are mostly traditional high polymer materials such as polycarbonate and polymethyl methacrylate. Although these materials have good mechanical properties and light transmittance, they are difficult to degrade.
[0003] The prior art CN111273459A discloses a microwave protective transparent medium material, which comprises, in sequence, a polycarbonate substrate, a first titanium pentoxide matching layer, a first silver conductive layer, a second titanium pentoxide matching layer, a second silver conductive layer, a third titanium pentoxide matching layer, a third silver conductive layer, a fourth titanium pentoxide matching layer, an aluminum oxide adhesive layer and a silicon dioxide wear-resistant layer. Three induced transmission filters effectively improve the protection against microwaves, with an average shielding effectiveness SE>18dB; the peak transmittance of visible light is ≥50%, the single-eye visual field in the vertical and horizontal directions is not less than 40, and the haze of the prepared microwave protective lens surface is not more than 2.0%. However, the application still uses polycarbonate material, which is not degradable. In addition, polycarbonate material is hard and brittle, and does not have sufficient flexibility. At the same time, its light transmittance is still lower than that of glass.
[0004] The prior art CN115466536A discloses a composition with ultraviolet spectrum shielding effect, which is prepared from avobenzone, sanshool or a derivative thereof. The composition has good ultraviolet absorption capacity for the entire ultraviolet band, widens the spectral absorption range, and can effectively resist ultraviolet radiation. However, the composition also causes the light transmittance of visible light to decrease.
[0005] With the continuous improvement of environmental awareness, the research and application of degradable high polymer materials have become a hot spot. Degradable polymers such as polylactic acid and polyhydroxyalkanoate have good biodegradability and biocompatibility, but they still have certain deficiencies in mechanical properties, light transmittance and the like, and are difficult to directly meet the use requirements of protective eyewear. For example, polylactic acid is brittle and has poor impact resistance; the light transmittance of polyhydroxyalkanoate needs to be further improved. Therefore, it is of important practical significance to develop a protective eyewear material that has good degradability, high light transmittance and excellent mechanical properties. SUMMARY
[0006] In order to overcome the above-mentioned deficiencies of the prior art, the present application aims to provide a degradable high-transparency protective eyewear material and a preparation method thereof.
[0007] In a first aspect, the present application provides a degradable high-transparency protective eyewear material, comprising the following components by weight parts: 100-150 parts of a polymer, 10-15 parts of a crosslinking agent, and 0.3-2 parts of an initiator.
[0008] The polymer is prepared from monomer A: 4,4'-dithiodibenzoic acid, monomer B: tetrafluoroterephthalic acid dimethyl ester, monomer C: vinyl terephthalic acid dimethyl ester, and monomer D: bisphenol A.
[0009] The specific preparation method of the polymer is as follows:
[0010] The monomers A, B, C, and D are dissolved in sulfolane in a certain amount, a catalyst is added, and stirring is performed at 100-400 rpm under vacuum conditions. In the first stage, heating is performed at 120-140°C for 1-4 h. In the second stage, heating is performed at 140-160°C for 2-5 h. In the third stage, heating is performed at 160-200°C for 1-5 h. The product is washed with a weak acid solution, washed with water, and dried to obtain the product.
[0011] The molar ratio of the amounts of the monomers A, B, C, and D is (15-20):(20-30):(10-15):(45-65), and preferably the molar ratio of the amounts is (16-18):(25-26):(11-12):(50-55).
[0012] The catalyst is selected from at least one of potassium carbonate, sodium carbonate, and sodium hydroxide, and is preferably potassium carbonate or sodium carbonate.
[0013] The vacuum condition is preferably a vacuum degree of less than 0.01 MPa.
[0014] The crosslinking agent is selected from at least one of diallyl disulfide and allyl propyl disulfide.
[0015] The initiator is selected from at least one of dibenzoyl peroxide, di-tert-butyl peroxide, cumene peroxide, and tert-butyl benzene peroxide.
[0016] In a second aspect, the present application provides a preparation method of a degradable high-transparency protective eyewear material, and the method is a melt co-extrusion method.
[0017] The melt co-extrusion method comprises the following specific steps:
[0018] The polymer 100-150 parts and the crosslinking agent 10-15 parts in the first aspect are added into a high-speed mixer, under vacuum conditions, the temperature is pre-set to 120-160 DEG C, the rotating speed is set to 500-1500 rpm, and stirring is carried out for 1-10 min, then the initiator is added, the rotating speed is set to 1000-1500 r / min, and mixing is carried out for 1-5 min, so as to obtain a mixture. The feeding rotating speed is set to 20-40 rpm, the mixture is injected into a double-screw extruder, the temperature of each zone of the extruder barrel is 160 DEG C, 170 DEG C, 170 DEG C, 170 DEG C, 170 DEG C, 170 DEG C, 170 DEG C, 170 DEG C (the temperature of the die head), the rotating speed of the main machine is 200-300 r / min, and the vacuum degree of the vacuum section is set to 0.04-0.08 MPa, then extrusion and drying are carried out, and the degradable high-transparency protective eyewear material is obtained.
[0019] Compared with the prior art, the application has the following technical effects:
[0020] The application provides a degradable high-transparency protective eyewear material and a preparation method thereof.
[0021] The polymer is copolymerized from monomers A, B, C and D with similar benzene ring structures, the chemical structural formulas of the monomers are different and similar, the feature ensures the relative uniformity of the internal structure of the polymer material copolymerized from different monomers, and prevents the appearance of crystalline regions, and further improves the light transmittance of the material; the light transmittance principle of the polymer is that the different benzene ring structures ensure the disordered and relatively uniform arrangement structure of molecular chains, the material surface is smooth and uniform, the diffuse reflection of visible light is reduced, and the structural differences of the monomers prevent the crystallization of the molecular chains in the material and reduce the scattering of visible light. In addition, the monomer A (4,4'-dithiodibenzoic acid) contains a disulfide bond, which can effectively enhance the flexibility and degradability of the material; the monomer B (tetrafluoro-p-xylylene dimethyl terephthalate) has a low polarizability, which reduces the absorption of visible light of the material and is beneficial to improving the light transmittance; and the monomer C (vinyl p-xylene dimethyl terephthalate) can be crosslinked with the crosslinking agent through the vinyl group, and further improve the strength and self-repairing performance of the material.
[0022] The crosslinking agent has a disulfide bond which is easy to degrade, and can further improve the strength performance of the material and retain the degradability of the material.
[0023] The degradable high-transparency protective eyewear material prepared by the application can improve the protection (hardness, strength, flexibility and other properties), high light transmittance and degradable environmental protection performance of the material through the synergy of the raw materials. BRIEF DESCRIPTION OF DRAWINGS
[0024] Figure 1 is a synthetic flow chart of the polymer.
[0025] Figure 2 is an infrared spectrogram of the polymer 1. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. The described embodiments are only some preferred embodiments of the present application, but not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0027] In the embodiments, the experimental methods used are conventional or general methods in the art if no special description is made, and the materials, reagents and the like used are commercially available if no special description is made.
[0028] The raw materials used in the examples and comparative examples are described as follows:
[0029] Diallyl disulfide: purchased from Jining Xinhe Chemical Co., Ltd.;
[0030] Allyl propyl disulfide: purchased from Shanghai Zhenyue Biological Technology Co., Ltd.;
[0031] 4,4'-dithiodibenzoic acid: purchased from Jilin Zhongke Chemical Technology Co., Ltd.;
[0032] Tetrafluoro terephthalic acid dimethyl ester: tetrafluoro terephthalic acid dimethyl ester;
[0033] Vinyl terephthalic acid dimethyl ester: purchased from Jilin Zhongke Chemical Technology Co., Ltd.;
[0034] Bisphenol A: purchased from Jinan Liyan Chemical Co., Ltd.;
[0035] Di-tert-butyl peroxide: purchased from Chengdu Makalh Chemical Co., Ltd.
[0036] The component raw materials used in the embodiments and comparative examples of the present application are commercially available unless otherwise specified, and the component raw materials used in each parallel experiment are the same.
[0037] Polymer preparation (self-made):
[0038] The monomers A, B, C and D are dissolved in sulfolane (anhydrous) in a certain amount, the volume of sulfolane is 4 times (mL / g) of the total mass of monomers A, B, C and D, potassium carbonate is added (the molar amount is 1.1 times of the molar amount of monomer D), under vacuum condition (less than 0.01 MPa, which is beneficial to remove oxygen and water and methanol generated in the reaction), 200 rpm stirring, the first stage is heated at 120℃ for 3h; the second stage is heated at 150℃ for 3h; the third stage is heated at 170℃ for 2h. Stop the reaction, reduce to room temperature, the product is washed with weak acid (1% acetic acid) solution to remove salt, water washing, 40℃ vacuum drying, to obtain the product. (The specific amount of polymer preparation raw materials is shown in Table 1).
[0039] Table 1 Amount of polymer preparation raw materials (molar amount parts)
[0040]
[0041] Example 1
[0042] A preparation method of a degradable high-transparency protective eyewear material, comprising the following specific steps:
[0043] Polymer 1 (self-made) 120 parts, allyl propyl disulfide (crosslinking agent) 12 parts are added into a high-speed mixer, under vacuum condition, the temperature is preset to 140℃, the rotation speed is set to 800 rpm for stirring for 5 min, dicumyl peroxide (initiator) 0.5 parts is added, the rotation speed is set to 1000 rpm for mixing for 2 min, to obtain a mixture. The feeding speed is set to 20-40 rpm, and the mixture is injected into a twin-screw extruder, wherein the temperature of each zone of the extruder barrel is 160℃, 170℃, 170℃, 170℃, 170℃, 170℃, 170℃, 170℃ (die temperature), the main machine rotation speed is 200 rpm, and the vacuum degree of the vacuum section is less than 0.08 MPa; extrusion, 40℃ vacuum drying for standby, to obtain the product.
[0044] Examples 2-4
[0045] Examples 2-4 and the preparation method of Example 1 are the same, except that the components or the amount of components are adjusted.
[0046] Comparative Examples 1-4
[0047] Comparative Examples 1-4 and the preparation method of Example 1 are the same, except that the components or the amount of components are adjusted.
[0048] Table 2 Example, comparative example ingredient ratio (weight parts)
[0049]
[0050]
[0051] I. Basic performance verification test
[0052] Visible light transmittance (%) was determined according to GB10810.3-2006 "Spectacle lenses and related spectacle products - Part 3: Transmittance specification and measurement methods".
[0053] The elongation at break was determined according to the provisions of GB / T1040.1-2018 "Determination of tensile properties of plastics".
[0054] The bending strength was tested according to GB / T9341-2008 "Determination of flexural properties of plastics".
[0055] The Shore D hardness was determined according to GB / T2411-2008 "Determination of indentation hardness by durometer for plastics and ebonite".
[0056]
[0057] According to the above table: 1) The degradable high-transmittance protective eyewear materials prepared in Examples 1-4 have high light transmittance. The visible light transmittance of Comparative Examples 1-3 is lower than that of Example 1. The reason may be that the comparative polymer is only polymerized from three of monomers A, B, C and D, and compared with the polymer 1 (polymer used in Example 1), the reduction of monomer types leads to the reduction of the dispersion uniformity of different monomers in the polymer, which affects the transmittance of visible light. Secondly, as shown in Comparative Example 2, the low polarizability of monomer B (tetrafluoro terephthalic acid dimethyl ester) reduces the absorption of visible light by the material, which is beneficial to improve the visible light transmittance. The visible light transmittance of Comparative Example 4 is lower than that of Example 1, which may be related to the fact that the comparative polymer 4 does not contain a crosslinking agent, resulting in a relatively uneven distribution of the polymer 1, which in turn affects the light transmittance of visible light. 2) The materials prepared in Examples 1-4 have good tensile strength and tensile elongation at break. The comparative polymer 1 contained in Comparative Example 1 lacks double sulfur bonds, resulting in a lack of flexibility and self-repairing ability of the material prepared in Comparative Example 1, so the tensile elongation at break of Comparative Example 1 is significantly lower than that of Example 1. The tensile elongation at break of Comparative Example 3 is superior to that of Example 1, which is related to the fact that the comparative polymer 3 (not containing an alkene group that can be crosslinked) does not undergo crosslinking, and the crosslinking agent itself undergoes polymerization. 3) Examples 1-4 have significant advantages in bending strength or hardness over Comparative Examples 1-4, which indicates that the crosslinking agent can significantly improve the bending strength and hardness of the material. Although Comparative Examples 1 and 4 also exhibit good hardness, their bending strength is significantly lower than that of Examples. In summary, the degradable high-transmittance protective eyewear materials described in Examples 1-4 have high light transmittance, high strength, hardness and toughness, and the protective eyewear prepared therefrom can effectively prevent impact damage while maintaining high light transmittance.
[0058] II. Soil degradation experiment
[0059] Collect the surface soil (0-20cm) of wild field, remove impurities through 2mm sieve, and determine the basic physicochemical properties (pH 6.5-7.5, organic matter content 3%-5%, water content 20%-30%); microbial activation: add a small amount of glucose (0.5% w / w) to the soil to promote microbial reproduction, and pre-culture for 3 days.
[0060] Sample treatment: cut the material into 1cm×1cm fragments, bury in soil (depth 5cm), 3 parallel groups.
[0061] Environmental parameters: temperature 25±1℃, dark culture (avoid light interference), and regularly supplement water to maintain the water content in the range of 20%-30%.
[0062] Detection index: weight loss rate: take out the sample after 12 months, dry and weigh after cleaning the residual soil, and calculate: degradation rate=(initial weight-residual weight) / initial weight×100%.
[0063] Example 1 Example 2 Example 3 Example 4 12 month degradation rate (%) 43.5 39.6 48.3 42.7
[0064] According to the data in the above table, the degradable high-transparency protective eyewear material prepared in Examples 1-4 has good biodegradability, which is due to the rich degradable disulfide bonds in the prepared material.
[0065] The preferred embodiments of the application disclosed above are only used to help explain the application. The preferred embodiments do not describe all the details, and the application is not limited to the specific embodiments described. Obviously, many modifications and changes can be made according to the content of the specification. The specification selects and describes these embodiments in order to better explain the principles and practical applications of the application, so that those skilled in the art can well understand and utilize the application. The application is limited only by the claims and their entire scope and equivalents.
Claims
1. A degradable high-transparency protective eyewear material, characterized in that, By weight parts, including the following components: polymer 100-150 parts, crosslinking agent 10-15 parts, initiator 0.3-2 parts; The polymer is prepared from monomer A: 4,4'-dithiodibenzoic acid, monomer B: tetrafluoroterephthalic acid dimethyl ester, monomer C: vinyl terephthalic acid dimethyl ester and monomer D: bisphenol A.
2. The degradable high-transparency protective eyewear material according to claim 1, characterized in that, The preparation method of the polymer is as follows: Dissolve monomers A, B, C and D in sulfolane by weight, add catalyst, stir at 100-400 rpm under vacuum, heat at 120-140℃ for 1-4h in the first stage, heat at 140-160℃ for 2-5h in the second stage, heat at 160-200℃ for 1-5h in the third stage, wash the product with weak acid solution, water and dry, and the product is obtained.
3. The degradable high-transparency protective eyewear material according to claim 2, characterized in that, In the preparation method of the polymer, the molar ratio of monomers A, B, C and D is (15-20):(20-30):(10-15):(45-65).
4. The degradable high-transparency protective eyewear material according to claim 2, characterized in that, The catalyst in the preparation method of the polymer is selected from at least one of potassium carbonate, sodium carbonate and sodium hydroxide.
5. The degradable high-transparency protective eyewear material according to claim 2, characterized in that, The vacuum degree of the vacuum condition is less than 0.01 MPa.
6. The degradable high-transparency protective eyewear material according to claim 1, wherein, The crosslinking agent is selected from at least one of diallyl disulfide and allyl propyl disulfide.
7. The degradable high-transparency protective eyewear material according to claim 1, wherein, The initiator is selected from at least one of dibenzoyl peroxide, di-tert-butyl peroxide, cumene peroxide and tert-butyl benzene peroxide.
8. The method for preparing the biodegradable high-transparency protective eyewear material according to any one of claims 1-7, characterized in that, Prepared by melt co-extrusion method.
9. The production method according to claim 8, characterized by, The melt co-extrusion method comprises the following steps: Add the polymer and crosslinking agent to a high-speed mixer, set the temperature to 120-160℃ and the rotation speed to 500-1500 rpm under vacuum, stir for 1-10 min, add the initiator, mix for 1-5 min at a rotation speed of 1000-1500 r / min to obtain a mixture; set the feeding speed to 20-40 rpm, inject the mixture into a double-screw extruder, set the temperature of each zone of the extruder barrel to 160℃, 170℃, 170℃, 170℃, 170℃, 170℃, 170℃, 170℃ (die temperature), set the main machine rotation speed to 200-300 r / min, and set the vacuum degree of the vacuum section to 0.04-0.08 MPa; extrude and dry, and the product is obtained.
Citation Information
Patent Citations
Microwave protection transparent dielectric material and preparation method and application thereof
CN111273459A
Composition with ultraviolet spectrum shielding effect and photoprotective coating
CN115466536A